Uczeń ze specyficznymi trudnościami w uczeniu się w procesie uczenia się i nauczania języków obcych w Polsce - Jaworska, Mariola (Neofilolog, 2019)
The article addresses the problem of teaching foreign languages to child-ren and adolescents with particular learning difficulties, which require specialized help from the state and the school as an institution. The dis-cussion includes the analysis of the current legal situation as well as the analysis of the organization and functioning of schools and psychological-pedagogical counseling service.